Bias and Discrimination: What Do We Know? - Marina Della Giusta; Steven J. Bosworth (Institute of Labor Economics (IZA), 2020)
The paper presents the economic literature on gender bias, illustrating the underpinnings in the psychology of bias and stereotyping; the incorporation of these insights into current theoretical and empirical research in economics, and the literature on methods to contrast bias presenting evidence (where it exists) of their effectiveness. The second part of the paper presents results of an experiment in revealing unconscious bias.
Keywords: D9; J7; 330; discrimination; gender; unconscoius bias; licensing